1998
DOI: 10.1016/s0921-4526(98)00446-3
|View full text |Cite
|
Sign up to set email alerts
|

Torsional oscillator studies of the superfluidity of 3He in aerogel

Abstract: We have made simultaneous torsional oscillator and transverse NMR measurements (at ∼ 165 kHz) on 3 He contained within aerogels with nominal densities of 1% and 2% of solid glass. The superfluid transition is seen simultaneously by both techniques and occurs at a temperature which agrees semi-quantitatively with that expected for homogeneous isotropic pair-breaking scattering of 3 He atoms by strands of silica. Values obtained for the superfluid density ρ s in the 2% sample are in reasonable agreement with tho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 10 publications
2
16
0
Order By: Relevance
“…The temperature variation of the inferred superfluid fraction in the aerogel is qualitatively similar to, but significantly higher than, that found by torsional oscillator experiments at higher temperatures, showing r s ͞r increasing more gradually with decreasing temperature below T c than that of the bulk B phase. The transition temperatures are consistent with other measurements made of 98% aerogel samples [7]. Superfluidity is not observed in our sample at pressures below about 2.7 bars.…”
supporting
confidence: 93%
“…The temperature variation of the inferred superfluid fraction in the aerogel is qualitatively similar to, but significantly higher than, that found by torsional oscillator experiments at higher temperatures, showing r s ͞r increasing more gradually with decreasing temperature below T c than that of the bulk B phase. The transition temperatures are consistent with other measurements made of 98% aerogel samples [7]. Superfluidity is not observed in our sample at pressures below about 2.7 bars.…”
supporting
confidence: 93%
“…The first NMR experiments 8,9,60,61) showed that paramagnetic solid 3 He, adsorbed on the aerogel surface, dominated the temperature dependent magnetization and consequently reduced the NMR frequency shifts substantially by the ratio of the liquid to the total magnetization according to a model for fast exchange. These effects can be allowed for in the measurement as is the case for NMR data in Fig.…”
Section: Identification Of the Superfluid State And Phase Diagrammentioning
confidence: 99%
“…9) Identification of the symmetry of the observed phases was not possible from measurements of the superfluid density with the torsional oscillator technique. 7) On the other hand early experiments on NMR frequency shifts and spectra were interpreted either as an equal-spin-pairing (ESP) state, 8) like the A-phase with a uniform texture (dipole-locked); or the B-phase with an inhomogeneous texture 60) determined by sample shape (dipole-unlocked). It seems likely that these very different results and their interpretation are a consequence of metastability of the A-like phase and differences between the samples.…”
Section: Identification Of the Superfluid State And Phase Diagrammentioning
confidence: 99%
“…Previous torsional oscillator experiments have been affected by the presence of spurious resonances resulting from composite modes of 3 He and aerogel whose frequency crosses the resonant frequency of the cell [1,6]. The strength of these resonances grow as the porosity of the aerogel sample increases, affecting the quality of data [1,5,6].…”
mentioning
confidence: 99%
“…Because the Cooper pairs in 3 He form in a p-wave state, quasiparticle scattering from the aerogel strands is pairbreaking [3]. Thus the 3 He-in-aerogel system is well suited to the exploration of the effect of impurity scattering and disorder on the superfluid transition and phase diagram.The superfluidity of 3 He in silica aerogel has been studied using torsional oscillators [1,[4][5][6], NMR [2,6-9] and sound propagation [10,11] techniques. These measurements show that both the superfluid transition temperature (T c ) and superfluid density (ρ s ) of the 3 He are suppressed by the disorder, but that the transition remains sharp [1].…”
mentioning
confidence: 99%